The role of traditional leaders in local government - Lebese, Potane Silas (My University, 2001)
Refer to the document
Thesis (MPA.) -- University of Limpopo, 2001
Keywords: Local government; Traditional leaders; Local government -- South Africa; Tribal government -- South Africa; Chiefdoms -- South Africa; Political participation -- South Africa